Exploring the architectural elements meaning of Masjid Agung Kubah Timah in Pangkalpinang City - Putra, Hadi Jaya; Octavia, Linda (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The research explores the architectural significance of Masjid Agung Kubah Timah (MAKT) in Pangkalpinang City, Indonesia. Designed by renowned architect Ridwan Kamil, MAKT represents a modern synthesis of Islamic architecture, local culture, in contemporary design. The aim is to foster a deeper appreciation of the architectural significance of MAKT. The study employs a qualitative approach to analyze MAKT's architectural elements. This study has done exploring its unique features such as the Tudung Saji-inspired dome, arch portals, Mihrab, and decorative elements. Departing from traditional mosque norms, MAKT's distinctive dome design draws inspiration from the tudung saji, a local food cover, adding a layer of cultural symbolism. The richness of Islamic art through Islamic Architecture in MAKT is evident in the integration of calligraphy and geometric patterns on the Mihrab and decorative elements, encapsulating the depth of Islamic theology. Results reveal a harmonious fusion of Islamic Architecture and Pangkalpinang's cultural identity in the mosque's design. MAKT stands as an iconic building, embodying a harmonious blend of tradition and modernity, contributing to the architectural diversity and cultural richness of Pangkalpinang.